Association between illegal use of substances and suicidal behavior in school students: An integrative review of empirical data - Karanikola, Maria; Zisimou, Prodromoula; Nystazaki, Maria; Zafiropoulou-Koutrouba, Anna; Severinsson, Elisabeth (My University, 2019)
Purpose: Investigation of the association between type of suicidal behavior and type and frequency of illegal use of substances (IUS) among school students (aged between 12 and 18 years), with a focus on gender differences. Design and Methods: A systematic review in PubMed, CINAHL, PsychINFO, and Scopus was performed. Identified articles were published between 2007 and 2018. Results: Twenty empirical studies confirmed the association between IUS and suicidality, strongly differentiated between males and females, highlighting the importance of gender-specific mediating factors. Conclusions: Mental health nurses need to document gender factors, frequency, and motivation of IUS when screening adolescents experiencing suicidal behavior and IUS.
Keywords: Adolescents; Substance use; Suicidal behavior; Suicidality